Rational use of energy and photovoltaic generation: sustainable strategies for northern Brazil - Nascimento Neto, Manoel; Fernandes Filho, Guilherme Eugênio Filippo [UNESP]; Muniz Junior, Jorge [UNESP]; da Rocha, Aglaé Baptista Torres [UNESP]; de Oliveira, Otávio José [UNESP] (FapUNIFESP (SciELO), 2025)
Concern about energy efficiency and renewable energy has emerged during the global energy crisis. This issue is particularly relevant in Roraima, a state in northern Brazil, due to its dependence on isolated electrical systems. Boa Vista, the capital, has high average annual temperatures and the country's highest average residential electricity consumption, which creates an opportunity for sustainable solutions. Given the abundant availability of solar radiation in the region, photovoltaic energy has emerged as a promising alternative for meeting energy demands sustainably and economically. In this work, case studies in three homes and on a university campus in Boa Vista made it possible to analyze the energy infrastructure and challenges and propose solutions to increase energy efficiency in the state and the region. The novelty of this work lies in integrating academic perceptions about energy efficiency and photovoltaics with practical initiatives implemented on campus. The study contributes to the theoretical-scientific discourse by exploring innovative strategies to increase energy efficiency and the use of photovoltaics, helping to advance the state of the art in this field. The managerial-applied contribution guides authorities in formulating policies for technological development and the rational use of energy.
Uso racional de energia e geração fotovoltaica: estratégias sustentáveis para o norte do Brasil
Keywords: Distributed photovoltaic generation; Energy efficiency; Photovoltaic energy; Sustainable energy supply